Game evolution and simulation analysis of power battery recycling in China under conflicting supply and demand of critical metals - Guo, Shaobo; Liu, Guwang; Guo, Xiaoqian; Wang, Yue (Frontiers in Energy Research, 2022)
A great demand for lithium, cobalt, nickel, and other critical metals by power batteries has been increasing with the explosive development of the new energy industry, which further exacerbated the contradiction between the supply and demand of critical metals. In addition, two key factors, including an imbalance of government reward and punishment and a low degree of cooperation between manufacturers and recycling enterprises, have hindered the recovery and utilization of critical metals in power battery with the expansion of the power battery recycling market. A three-party evolutionary game model, including power battery manufacturers, third-party recycling enterprises, and the government, was constructed in this study to analyze the evolutionary stability of the strategy selection of each participant. Also, the influence of each factor on the three-party strategy selection and verifying the reliability of the results through simulation were also discussed. The results show that 1) both government incentives and punishments are beneficial for promoting cooperation between power battery manufacturers and recycling enterprises. The cost of cooperation will be the key factor affecting power battery recycling. 2) Increasing the probability of cooperation is an effective way to ensure the increase in income of both parties after cooperation. Further suggestions, including the establishment of a dynamic reward and punishment mechanism by the government and strengthening the cooperation to cope with the continued tight supply of critical metals by the manufacturers and recyclers, were also put forward in this research.